Study of the influence of post-harvest treatment with salicylic acid and chitosan on the storage of blueberries (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
Formulation of the problem Preservation of the quality of berry raw materials is becoming relevant due to the value of berries as a food product for dessert and technological purposes in the processing industry.To reduce berry losses throughout the entire logistics chain "harvest - post-harvest processing of berry raw materials - transportation - storage - sale", it is necessary to slow down the evaporation of water from the fruits, prevent possible physiological damage and microbiological spoilage of products. For this purpose, pre-treatment of berries before storage with preparations that have antibacterial properties is used. A new technology for post-harvest processing of fruit and berry products with edible coatings is being introduced.Methods of post-harvest processing of fruit and berry products are being searched for, which inhibit physiological processes during storage and extend the duration of storage. Storing berries with minimal weight loss and without deterioration in quality is a pressing issue.Purpose. The conducted research aimed to study the effect of pre-treatment of blueberries with a solution of salicylic acid and chitosan on their preservation. To achieve this goal, it was necessary to solve the following tasks: to determine the natural weight loss of blueberries during storage; to establish the change in dry soluble substances of blueberries, taking into account weight loss during their treatment with a solution of salicylic acid and chitosan.The object of the study is the technology of pre-treatment of blueberries with the use of salicylic acid and chitosan.The subject of the study is blueberries and a solution of salicylic acid and chitosan.Conclusions. Treatment of berries with a solution of salicylic acid and chitosan extends the storage time by 7 days and reduces weight loss. Berries of the Duke variety reduced weight loss by 8.9% (from 19.2% to 10.3%), similar results were obtained for the Patriot variety – 8.5% (from 22.8% to 14.3%), other varieties varied in weight loss from 6.2 to 5.3%.  Pretreatment of blueberries with salicylic acid and chitosan slowed down the loss of dry soluble substances by 2.3–3.8% depending on the characteristics of the variety, while in untreated berries by 2.8–4.9%. The greatest loss of dry soluble substances was observed in the Patriot blueberry variety, while in the Liberty variety they were the smallest – 2.8%
Keywords: postharvest treatment; salicylic acid; chitosan; edible coatings; weight loss